Análisis de cartera en riesgo y su incidencia en la COAC Mushuk Yuyay Ltda. periodo 2020. - Fajardo Orellana, Lourdes Magaly (2023)
In this research work, entitled: ANALYSIS OF PORTFOLIO AT RISK AND ITS INCIDENCE ON THE LIQUIDITY OF THE COAC MUSHUK YUYAY OF THE CITY OF CAÑAR", PERIOD 2020, its purpose is to analyze the effect of the credit portfolio at risk on the Liquidity of the cooperative, and the measures that are taken to be able to continue providing its services to society and generating profits for it. This investigation consists of 5 chapters, which are distributed as follows. Chapter I. Referential framework. Chapter II deals with the theoretical framework, which is divided into two sections. The first consists of previous investigations with similar topics, and the second with the theoretical foundation. In Chapter III, it refers to the methodology that was carried out in the investigation and the different points to follow, among them is, type of investigation, investigation design, focus, and level of investigation, thus carrying out a detailed work. . In Chapter IV it consists of the analysis and discussion of the results obtained and finally we have Chapter V, the same one that details conclusions and recommendations that have been obtained throughout the investigation.